Temporal association between drops in thoracic impedance and malignant ventricular arrhythmia: A longitudinal analysis of remote monitoring trends. (14th February 2023) - Rodio, Giovanna; Iacopino, Saverio; Pisanò, Ennio C.; Calvi, Valeria; Rovaris, Giovanni; Marini, Massimiliano; Giammaria, Massimo; Caravati, Fabrizio; Maglia, Giampiero; Zanotto, Gabriele; Della Bella, Paolo; Biffi, Mauro; et al.
Abstract: Introduction: Thoracic impedance (TI) drops measured by implantable cardioverter‐defibrillators (ICDs) have been reported to correlate with ventricular tachycardia/fibrillation (VT/VF). The aim of our study was to assess the temporal association of decreasing TI trends with VT/VF episodes through a longitudinal analysis of daily remote monitoring data from ICDs and cardiac resynchronization therapy defibrillators (CRT‐Ds). Methods and Results: Retrospective data from 2384 patients were randomized 1:1 into a derivation or validation cohort. The TI decrease rate was defined as the percentage of rolling weeks with a continuously decreasing TI trend. The derivation cohort was used to determine a TI decrease rate threshold for a ≥99% specificity of arrhythmia prediction. The associated risk of VT/VF episodes was estimated in the validation cohort by dividing the available follow‐up into 60‐day assessment intervals. Analyses were performed separately for 1354 ICD and 1030 CRT‐D patients. During a median follow‐up of 2.0 years, 727 patients (30.4%) experienced 3298 confirmed VT/VF episodes. In the ICD group, a TI decrease rate of >60% was associated with a higher risk of VT/VF episode in a 60‐day assessment interval (stratified hazard ratio, 1.42; 95% confidence interval (CI), 1.05–1.92; p  = .023). The TI decrease preceded (40.8%) or followed (59.2%) the VT/VF episodes. In the CRT‐D group, no association between TI decrease and VT/VF episodes was observed ( p  = .84). Conclusion: In our longitudinal analysis, TI decrease was associated with VT/VF episodes only in ICD patients. Preventive interventions may be difficult since episodes can occur before or after TI decrease.